Fluctuations in Phenolic Content and Antioxidant Capacity of Green Vegetable Juices during Refrigerated Storage - Kim, Seong Yeong (Prev Nutr Food Sci, 2015)
Shinseoncho and kale were made into green vegetable juices by building block [shinsenocho branch (SB), shinsenocho leaf (SL), kale branch (KB), and kale leaf (KL)]. Fluctuations in their phenolic contents and antioxidant capacities were analyzed during refrigerated storage at 4°C for 28 days. Total polyphenolic contents of leaf parts showed a decreasing tendency after 4 days (SL) or 7 days (KL), whereas branch parts showed fluctuating values during the entire storage period. The 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging capacity was rapidly decreased in SB and in SL at 28 days (P<0.001), whereas KL showed a slightly increasing tendency after 14 days. For the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity, SL showed a sharp fall at 28 days (P<0.001), and KL showed a decreasing tendency after 14 days (P<0.001). SB showed a steady decrease during the entire storage period and KB indicated a nearly zero (0.97%) at 28 days. Pearson’s coefficients for the correlation between antioxidant capacities measured by the ABTS and DPPH assays, and the total polyphenolic contents were determined. The results showed that the ABTS assay (r=0.934, P<0.001) was more strongly positively correlated with the total phenolic contents than the DPPH assay (r=0.630, P<0.001). In conclusion, when considering all building blocks, green vegetable juices, including kale and shinseoncho may have kept antioxidant capacities for up to 14 days under refrigeration, and the ABTS assay better reflects a positive correlation with the total phenolic contents when compared to the DPPH assay.